2016
DOI: 10.1016/j.virol.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retroviruses mobilized during friend murine leukemia virus infection

Abstract: We have demonstrated in a mouse model that infection with a retrovirus can lead not only to the generation of recombinants between exogenous and endogenous gammaretrovirus, but also to the mobilization of endogenous proviruses by pseudotyping entire polytropic proviral transcripts and facilitating their infectious spread to new cells. However, the frequency of this occurrence, the kinetics, and the identity of mobilized endogenous proviruses was unclear. Here we find that these mobilized transcripts are detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…While some studies have identified EnMuLVs participating in recombination with SFFVs and what the end results are, they do not show to what extent the recombinations are ongoing and how they shape viral population structure. Two studies have identified endogenous polytropic MuLV sequences being packaged into F-MuLV virions as a common occurrence in NFS/N mice; happening as early as 1 day post-infection (Evans et al, 2009;Boi et al, 2016). Thus, endogenous sequences appear to be primed to not only recombine and create new viral genotypes, but also to continuously alter the SFFV viral population by repeated introgressions.…”
Section: Sffv-enmulv Recombinantsmentioning
confidence: 99%
“…While some studies have identified EnMuLVs participating in recombination with SFFVs and what the end results are, they do not show to what extent the recombinations are ongoing and how they shape viral population structure. Two studies have identified endogenous polytropic MuLV sequences being packaged into F-MuLV virions as a common occurrence in NFS/N mice; happening as early as 1 day post-infection (Evans et al, 2009;Boi et al, 2016). Thus, endogenous sequences appear to be primed to not only recombine and create new viral genotypes, but also to continuously alter the SFFV viral population by repeated introgressions.…”
Section: Sffv-enmulv Recombinantsmentioning
confidence: 99%
“…Among positive effects are the expression of viral gene products as useful new genes in the host [ 6 ], modification of chromosomal gene expression by ERVs including promoter, enhancer, and insulator functions, as well as alternative splice signals from ERV integrations in host transcription units or adjacent to chromosomal genes [ 2 , 7 ]. On the other hand, is the potential for host gene disruption, as well as the potential for somatic spread of replicating retroviruses leading to pathogenic consequences for the host [ 2 , 8 , 9 ]. ERV-mediated genomic recombination can further contribute to the organization and plasticity of the host’s genome [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain MuLV strains may have specific interactions with endogenous MuLV. For example, infection with the Friend strain of MuLV (Friend-MuLV) in NFS/N mice has been documented to increase endogenous MuLV transcription (94). After infection with Friend-MuLV, spleens of infected mice were cocultured on a background of Fisher rat embryo cells to reduce the propensity of subsequent Friend-MuLV infection and limit mutations to mobilized Pmv.…”
Section: Endogenous and Exogenous Mulv Interactions Have Been Charact...mentioning
confidence: 99%
“…Pmv transcripts could be detected in Friend-MuLV-infected treatments one day post infection and persist for weeks. This process is likely to increase opportunities for recombination between Friend-MuLV and endogenous MuLV, which may contribute to pathogenesis and oncogenesis (94).…”
Section: Endogenous and Exogenous Mulv Interactions Have Been Charact...mentioning
confidence: 99%